Aerosol‐Spray Pyrolysis toward Preparation of Nanostructured Materials for Batteries and Supercapacitors. Issue 2 (5th December 2017) - Nie, Ping; Xu, Guiyin; Jiang, Jiangmin; Dou, Hui; Wu, Yuting; Zhang, Yadi; Wang, Jiang; Shi, Minyuan; Fu, Rurui; Zhang, Xiaogang
Abstract: There is an ever‐increasing demand for energy storage combined with high energy density, long lifespan, and low cost. Design and fabrication of electrode materials with characteristics of scale and fast charge (electrons and ions) access to electrochemically active site are of great importance. The aerosol‐spray synthesis technique has shown considerable promise as an attractive, cost‐effective, and scalable route for material preparation. Particles with complex architectures and chemistry can be produced by simply using an economical, continuous, and rapid process. Here, recent advances of the industrially viable aerosol‐spray‐pyrolysis method are summarized with regard to structure design and processing of electrode materials in the field of energy storage. Beginning with an introduction to the principles, characteristics, and process parameters of aerosol‐spray methods, the focus then moves to recent achievements to date in experimental exploration of fabricating a variety of electrode materials for energy‐storage devices, including lithium‐ion batteries, sodium‐ion batteries, supercapacitors, and lithium–sulfur batteries. Also discussed are the current status, directions, and prospects for future exploration of material synthesis using aerosol‐spray techniques. Aerosol‐spray pyrolysis represents an important breakthrough in multidimensional structure design, and exhibits incredible versatility for material fabrication for high‐performance energy‐storage devices. Abstract : The aerosol‐spray method represents an important breakthrough in multidimensional structure design, and exhibits incredible versatility for material preparation. Recent advances of the industrially viable aerosol‐spray‐pyrolysis method in material processing in the field of energy storage are summarized.